Islamic Banking in Pakistan - Shujaat A. Khan (International Institute of Islamic Thought, 1995)
The book under review is a revised edition of Muhammad Akram Khan's Islamic Banking in Pakistan. In this slender yet eloquent volume the author, who has many other published works in the field of Islamic economics and finance to his credit, examines a cornerstone of government policy during the early 1980s: the Islamization of banking in Pakistan. He gives a candid and coherent account of this major develop ment and asserts that it failed because of the lukewarm attitudes of the administration and political leadership as well as because of the perverted outlook of the bureaucrats, elites, and bankers. In the final analysis, he suggests some concrete measures that are designed to help policy makers and strategists in reconstructing the financial institutions within the framework of Islamic laws. The subject matter of this book has been divided into six chapters, which are preceded by Muzaffar Hussain's preface and followed by concluding remarks, endnotes, an exhaustive bibliography, and an index. In chapter one, Akram provides an historical overview of the process of Islamization of banking, makes some important observations, and draws logical conclusions. He points out that the Council of Islamic Ideology, a constitutional body consisting of scholars of all shades and schools of thought, categorically prohibited interest (riba) in all of its various forms. However, no sincere effort was ever made by the government to eliminate interest and to build an interest-free economy. The process of Islamization, which was initiated in the early 1980s and slowed down during the latter part of the decade, finally came to a complete halt in early 1992. The government, instead of invigorating the Islamization process, filed an appeal in the Supreme Court against the Shari'ah Court's decision calling for the abolition of all interest-based activities by June 1992. In chapter two, the author goes to the roots of the problem and shows that a lack of political will was the single most important factor causing the systematic failure of this experiment in Pakistan. He shows the futility of inconsistent policies and inappropriate strategies pursued by the State Bank of Pakistan, such as allowing banks to continue interest-based operations side by side with interest-free activities. Given freedom of choice, banks and other financial institutions showed a much higher interest in such interest-based financing techniques as mark-up and buy-back agreements and little or no interest in such modes of finance as musharakah, mudarabah, and ijarah, all of which are based on Islamic principles associated with profit-loss sharing. He observes that the situation was aggravated further when the government excluded the management of public finance from the jurisdiction of the Shari‘ah court and continued its own interest-based activities as usual ...